Pricing Strategy and Service Quality Improvement to Optimize Customer Satisfaction: a Systematic Literature Review - Noorsyah, Muhammad Naufal; Widyaningsih, Aristanti; Andriana, Denny (International Journal of Business, Law, and Education, 2024)
Customer satisfaction is a critical determinant of business sustainability and growth, influencing customer loyalty, company reputation, and competitive positioning. This study systematically reviews the interplay between pricing strategies and service quality as key drivers of customer satisfaction. Employing a Systematic Literature Review (SLR) method guided by the PRISMA framework, 25 relevant articles were analyzed to synthesize insights into this dynamic relationship. The findings reveal that effective pricing strategies, including value-based, competitive, and dynamic pricing, significantly impact customer satisfaction by aligning price with perceived value. Simultaneously, high service quality, measured through the SERVQUAL dimensions (reliability, responsiveness, assurance, empathy, and tangibles), enhances customer experiences and fosters loyalty. The study underscores the critical interdependence of these factors, demonstrating that businesses must balance competitive pricing with superior service delivery to optimize customer satisfaction. This research provides a framework for companies to strategically integrate pricing and service quality, addressing market-specific challenges and leveraging opportunities for long-term success. Future studies are encouraged to explore the role of technological advancements, such as AI-driven pricing models and personalized service innovations, in further enhancing customer satisfaction in dynamic and competitive markets.